Polityka pamięci w japońsko-chińskich stosunkach dyplomatycznych - Warchoł, Paulina (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The conflict concerning historical events between Japan and China is now more visible than ever before – once again the disputes over Senkaku/ Diaoyu islands have awakened the ghosts of the past and undermined Japanese-Chinese bilateral relations. The major problems in the politics of memory between those two Asian countries are the rape of Nanking, the content of Japanese textbooks and officials’ visits in Yasukuni shrine. While the tensions are rising, Japan and China struggle to establish historical facts and present their interpretations to the society.